2013
DOI: 10.1556/aphysiol.100.2013.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Better cardiorespiratory fitness associated with favourable metabolic control and health-related quality of life in youths with type 1 diabetes mellitus

Abstract: Objective: to explore the relationship among health-related quality of life (HRQoL), clinical variables, anthropometric measures, physical activity and cardiorespiratory fitness in children and adolescents with type 1 diabetes. Furthermore, we aimed to find predictors of HRQoL and metabolic control. Methods: A total of 106 patients (sex ratio: 1:1) with mean HbA1c of 8.55 (± 1.44) % and diabetes duration of 5.15 (± 3.24) years were assessed. The average age was 13.22 (± 3.08) years. Results: We observed statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…Using patient records from the 2002 to 2012 Calidad de Vida Center, Clennin et al [11] examined the relationship between CRF and HRQoL in a Uruguayan cohort at risk for developing cardiovascular disease (CVD) and found positive associations between CRF and several dimensions of HRQoL (women: vitality, physical health, physical role, bodily pain, and general health; men: physical health). In children and adolescents with type 1 diabetes, Lukács et al [31] examined associations among HRQoL, clinical profiles, anthropometric measures, and physical activity and CRF and found that good CRF was significantly associated with better HRQoL and favorable metabolic control among the youth. Similarly, this positive association between CRF and HRQoL was observed in community-dwelling older adults [32] and workers [33], as well as in patients with CVD [11], McArdle disease [34], severe mental illness [35], and survivors of cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…Using patient records from the 2002 to 2012 Calidad de Vida Center, Clennin et al [11] examined the relationship between CRF and HRQoL in a Uruguayan cohort at risk for developing cardiovascular disease (CVD) and found positive associations between CRF and several dimensions of HRQoL (women: vitality, physical health, physical role, bodily pain, and general health; men: physical health). In children and adolescents with type 1 diabetes, Lukács et al [31] examined associations among HRQoL, clinical profiles, anthropometric measures, and physical activity and CRF and found that good CRF was significantly associated with better HRQoL and favorable metabolic control among the youth. Similarly, this positive association between CRF and HRQoL was observed in community-dwelling older adults [32] and workers [33], as well as in patients with CVD [11], McArdle disease [34], severe mental illness [35], and survivors of cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…A testi fittség hozzájárul az életminőség javulásához is. 3 Ráadásul a megfelelő fizikai állapot nemcsak a már ismert és kezelt cukorbetegek számára hasznos, hanem a diabetes kialakulásának lehetőségét is csökkentheti. 4,5,6 Az 1-es típusú diabetesesekre fókuszálva azt látjuk, hogy gondozottjaink egy része tisztában van ugyan a testmozgás jótékony szerepével, de -a betegek nagyobb részére jellemzően -a hypoglykaemiától való félelem óvatosabbá teszi őket, ahogy arról többek között egy kanadai munkacsoport is beszámolt.…”
Section: Szenzorral Támogatott Inzulinpumpa Használata Extrém Fizikaiunclassified
“…A glykaemiás kontrollra csak a kardiorespiratorikus fittség volt szignifikáns befolyásoló hatással. 27 A jobb fizikai fittség és a kedvezőbb glykaemiás kontroll között a tanulmányok jelentős száma szoros kapcsolatot mutatott, 27,28,31,40,44,45,46 de találtunk néhány közlést, amelyben szignifikáns kapcsolat nem volt kimutatható. 41,47,48 Kiemelt figyelmet érdemel Aouadi vizsgálata, aki 33 diabeteses gyermeket 3 csoportba osztott.…”
Section: Fizikai Fittségunclassified